ОКРЕМІ ПИТАННЯ ВІДПОВІДАЛЬНОСТІ ЮРИДИЧНИХ ОСІБ ЗА ПРОПАГАНДУ ВІЙНИ - Пекар, Павло Васильович (SUPREMANCE OF LAW, 2017)
The article focuses on the question of liability of legal persons for the commission of an authorized person on behalf of and in the interests of crime under Art. 436 of the Criminal Code of Ukraine. We consider the activities of legal exposure limits and procedure for their application.